First PGT-A using human in vivo blastocysts recovered by uterine lavage: comparison with matched IVF embryo controls - Munné, Santiago; Nakajima, Steven T; Najmabadi, Sam; Sauer, Mark V; Angle, Marlane J; Rivas, José L; Mendieta, Laura V; Macaso, Thelma M; Sawarkar, Sarthak; Nadal, Alexander; Choudhary, Kajal; Nezhat, Camran; et al. (Human reproduction (Oxford), 2020)
Abstract STUDY QUESTION After controlled ovarian stimulation (COS) and IUI, is it clinically feasible to recover in vivo conceived and matured human blastocysts by uterine lavage from fertile women for preimplantation genetic testing for aneuploidy (PGT-A) and compare their PGT-A and Gardner scale morphology scores with paired blastocysts from IVF control cycles? SUMMARY ANSWER In a consecutive series of 134 COS cycles using gonadotrophin stimulation followed by IUI, uterine lavage recovered 136 embryos in 42% (56/134) of study cycles, with comparable in vivo and in vitro euploidy rates but better morphology in in vivo embryos. WHAT IS KNOWN ALREADY In vivo developed embryos studied in animal models possess different characteristics compared to in vitro developed embryos of similar species. Such comparative studies between in vivo and in vitro human embryos have not been reported owing to lack of a reliable method to recover human embryos. STUDY DESIGN, SIZE, DURATION We performed a single-site, prospective controlled trial in women (n = 81) to evaluate the safety, efficacy and feasibility of a novel uterine lavage catheter and fluid recovery device. All lavages were performed in a private facility with a specialized fertility unit, from August 2017 to June 2018. Subjects were followed for 30 days post-lavage to monitor for clinical outcomes and delayed complications. In 20 lavage subjects, a single IVF cycle (control group) with the same ovarian stimulation protocol was performed for a comparison of in vivo to in vitro blastocysts. PARTICIPANTS/MATERIALS, SETTINGS, METHODS Women were stimulated with gonadotrophins for COS. The ovulation trigger was given when there were at least two dominant follicles ≥18 mm, followed by IUI of sperm. Uterine lavage occurred 4–6 days after the IUI. A subset of 20 women had a lavage cycle procedure followed by an IVF cycle (control IVF group). Recovered embryos were characterized morphologically, underwent trophectoderm (TE) biopsy, vitrified and stored in liquid nitrogen. Biopsies were analyzed using the next-generation sequencing technique. After lavage, GnRH antagonist injections were administered to induce menstruation. MAIN RESULTS AND THE ROLE OF CHANCE A total of 134 lavage cycles were performed in 81 women. Uterine lavage recovered 136 embryos in 56 (42%) cycles. At the time of cryopreservation, there were 40 (30%) multi-cell embryos and 96 (70%) blastocysts. Blastocysts were of good quality, with 74% (70/95) being Gardener grade 3BB or higher grade. Lavage blastocysts had significantly higher morphology scores than the control IVF embryos as determined by chi-square analysis (P < 0.05). This is the first study to recover in vivo derived human blastocysts following ovarian stimulation for embryo genetic characterization. Recovered blastocysts showed rates of chromosome euploidy similar to the rates found in the control IVF embryos. In 11 cycles (8.2%), detectable levels of hCG were present 13 days after IUI, which regressed spontaneously in two cases and declined after an endometrial curettage in two cases. Persistent hCG levels were resolved after methotrexate in three cases and four cases received both curettage and methotrexate. LIMITATIONS, REASON FOR CAUTION The first objective was to evaluate the feasibility of uterine lavage following ovarian stimulation to recover blastocysts for analysis, and that goal was achieved. However, the uterine lavage system was not completely optimized in our earlier experience to levels that were achieved late in the clinical study and will be expected in clinical service. The frequency of chromosome abnormalities of in vivo and IVF control embryos was similar, but this was a small-size study. However, compared to larger historical datasets of in vitro embryos, the in vivo genetic results are within the range of high-quality in vitro embryos. WIDER IMPLICATIONS OF THE FINDINGS Uterine lavage offers a nonsurgical, minimally invasive strategy for recovery of embryos from fertile women who do not want or need IVF and who desire PGT, fertility preservation of embryos or reciprocal IVF for lesbian couples. From a research and potential clinical perspective, this technique provides a novel platform for the use of in vivo conceived human embryos as the ultimate benchmark standard for future and current ART methods. STUDY FUNDING/COMPETING INTEREST(S) Previvo Genetics, Inc., is the sole sponsor for the Punta Mita, Mexico, clinical study. S.M. performs consulting for CooperGenomics. J.E.B. and S.A.C. are co-inventors on issued patents and patents owned by Previvo and ownshares of Previvo. S.N. is a co-author on a non-provisional patent application owned by Previvo and holds stock options in Previvo. S.T.N. and M.J.A. report consulting fees from Previvo. S.T.N., S.M., M.V.S., M.J.A., C.N. and J.E.B. are members of the Previvo Scientific Advisory Board (SAB) and hold stock options in Previvo. J.E.B and S. M are members of the Previvo Board of Directors. A.N. and K.C. are employees of Previvo Genetics. L.V.M, T.M.M, J.L.R and S. S have no conflicts to disclose. TRIAL REGISTRATION NUMBER Protocol Registration and Results System (PRS) Trial Registration Number and Name: Punta Mita Study TD-2104: Clinical Trials NCT03426007.